Assisting anti-PD-1 antibody treatment with a liposomal system capable of recruiting immune cells. Issue 16 (10th April 2019) - Zhou, Boyang; Jiang, Qiongchao; Xiao, Xiaoyun; Xu, Xiaolin; Xu, Yanni; Kong, Yao; Zhang, Wenyue; Zeng, Yunting; Liu, Xiaodi; Luo, Baoming
Abstract : Less than 30% of patients exhibit durable therapeutic responses to anti-PD-1 antibodies. A liposomal system was synthesized to assist anti-PD-1 treatment. Abstract : Despite the functions of anti-PD-1 antibodies as immune checkpoint regulators, less than 30% of patients exhibit durable therapeutic responses to anti-PD-1 antibodies. Studies have shown that insufficient infiltration of immune cells might limit the outcome of anti-PD-1 therapy. Therefore, we synthesized an immune cell-recruiting liposomal system (FN-nps) to improve this therapeutic strategy. The FN-nps could generate cell debris and expose heat shock protein 70, which could recruit immune cells to tumor sites to assist in anti-PD-1 treatment. In vivo experiments revealed that the FN-nps could assist in anti-PD-1 therapy by increasing the number of lymphocytes in the peripheral blood and tumor site by generating tumor antigens, and this effect was accompanied by an increase in cytokine expression. The number of CTLs increased and mRNA expression levels of cytokines were regulated when the FN-nps were combined with anti-PD-1 therapy. The revealed properties of the liposomal system make it highly promising for assisting in anti-PD-1 antibody immunotherapy in different cancers.